2006
DOI: 10.1002/jor.20110
|View full text |Cite
|
Sign up to set email alerts
|

In vivo flexor tendon forces increase with finger and wrist flexion during active finger flexion and extension

Abstract: ABSTRACT:The effects of different hand motions and positions used during early protected motion rehabilitation on tendon forces are not well understood. The goal of this study was to determine in vivo forces in human flexor digitorum profundus (FDP) and flexor digitorum superficialis (FDS) tendons of the index finger during active unresisted finger flexion and extension. During open carpal tunnel surgery (n ¼ 12), flexor tendon forces were acquired with buckle force transducers, and finger positions were recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(47 citation statements)
references
References 30 publications
4
38
1
Order By: Relevance
“…A model with the musculotendon details to ascertain the muscle and tendon forces that produce the required torques is underway (Zhang et al, 2007). Preliminary results indicate the estimated peak forces are within the same order of magnitude (o10 N) as previously modelpredicted (Brook et al, 1995;Buchner et al, 1988;SanchoBru et al, 2001) or measured in vivo (Dennerlein et al, 1999;Kursa et al, 2006), thus lending some credence to the torque profiles resulting from the current study. Second, while the modeling scheme is believed to be general, the estimated model parameters and associated interpretations are specific to the movements studied here.…”
Section: Article In Presssupporting
confidence: 76%
“…A model with the musculotendon details to ascertain the muscle and tendon forces that produce the required torques is underway (Zhang et al, 2007). Preliminary results indicate the estimated peak forces are within the same order of magnitude (o10 N) as previously modelpredicted (Brook et al, 1995;Buchner et al, 1988;SanchoBru et al, 2001) or measured in vivo (Dennerlein et al, 1999;Kursa et al, 2006), thus lending some credence to the torque profiles resulting from the current study. Second, while the modeling scheme is believed to be general, the estimated model parameters and associated interpretations are specific to the movements studied here.…”
Section: Article In Presssupporting
confidence: 76%
“…First, we were only able to verify the model prediction regarding whether (instead of how) the FDS was activated during unloaded flexion. While it was not feasible for us to acquire in vivo finger muscletendon force data, in previous studies where such data were collected on patients awaiting open carpal tunnel release surgeries (Kursa et al, 2006;Nikanjam et al, 2007), the finger kinematic measurement was rather simplified (e.g., only the PIP and MCP angles were videographically measured). A rigorous and complete model validation is possible only when both high accuracy finger kinematics and tendon force data can be measured simultaneously in vivo, which remains a practical challenge.…”
Section: Discussionmentioning
confidence: 99%
“…Dennerlein et al (1999) showed that the FDS force ranged from 0 to 4 N before the fingertip touched the key during tapping. Kursa et al (2006) suggested both the FDS and FDP muscles were active during the index finger flexion. They reported that the mean FDS forces ranged from 1.3 to 8.5 N, respectively.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, finger movement also causes deformation of the median nerve, due to the compression from the surrounding soft tissues and the finger flexor tendon (Korstanje et al, 2010;Kursa et al, 2006;Loh et al, 2016a;Loh et al, 2016b;Ugbolue et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, repetitive finger movements could result in a higher shear strain between the median nerve and the sub synovial connective tissue (Kursa et al, 2006;Yoshii et al, 2008). However, the association between computer work and CTS remains inconclusive, and the pathophysiological relationship between keyboard typing activity and CTS remains questionable.…”
Section: Introductionmentioning
confidence: 99%